Perception and determinants of stigmatization of people with psoriasis in the German population. (21st July 2020) - Sommer, R.; Topp, J.; Mrowietz, U.; Zander, N.; Augustin, M.
Abstract: Background: Perception of psoriasis in the general population is characterized by knowledge deficits and prejudice against those affected. The extent and possible predictors of stigmatizing attitudes remain unclear. Objectives: The aim was to assess prejudices and stigmatization of people with psoriasis and to identify sociodemographic and attitude‐related variables accounting for stigmatization. Methods: Representative telephone surveys of 2004 (in 2017) and 2001 (in 2018) adults using a standardized questionnaire. Descriptive analyses were applied to living area, age, gender, educational status, general knowledge and attitudes about psoriasis. Logistic regression analyses were carried out to determine which variables are associated with the assessment of prejudices of 'others' against people with psoriasis. Those prejudices were specified by the following statements: 'they should take better care of themselves', 'don't want to touch people with psoriasis' and 'disgusted by psoriasis'. Results: The majority of those surveyed (74%) believe that people with psoriasis are disadvantaged. Similarly, a majority (69%) said that most people find psoriasis disgusting, do not want to touch people with psoriasis (59%) and think that people with psoriasis need to take better care of themselves (45%). 'Willing to enter a relationship with an affected person' (OR = 0.330, P = 0.029), higher age (OR = 1.027, P <0.001) and male gender (OR = 1.263, P = 0.034) proved to be significantly associated with 'psoriasis is disgusting'. Education (OR = 1.648, P = 0.016) and lower age (OR = 0.847, P <0.001) are significantly associated with 'they need to take better care of themselves'. Conclusions: Data suggest that stigmatization of skin diseases is still entrenched. This overview shows the need for interventions against stigmatization of those affected. Results imply that gender, age and education level and related health literacy of the target groups of respective interventions should be taken into account.